1992
DOI: 10.4141/cjas92-013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinomycin and enzyme supplementation on nutrient digestibility and the performance of pigs fed barley- or rye-based diets

Abstract: Pour les deux exp6riences, un indicateur de digestibilit6, I'oxyde de chrome (0.5%) 6tait incorpor6 durant 10 jours dans I'aliment de 4 ir 6 porcs par traitement dbs qu'ils avaient atteint le poids de 42 kg.Ni la pr6paration enzymatique, ni la salinomycine, seule ou en combinaison, n'a significativement am6lior6 la croissance ou I'indice de consommation des porcs, qu'ils soient nourris ir l'orge ou au seigle.Dans le r6gime h I'orge, I'incorporation des deux additifs a significativement (P<0,05) am6lior6 la dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
4
9
0
Order By: Relevance
“…p-Glucan is also highly digestible in the ileum of pigs (Graham et al 1986), apparently more digestible than starch (Graham et al 1989) (Thacker et al 1988(Thacker et al , 1992b (Thacker et al , 1992a It seems that the most likely application would be in weanling pig diets where pancreatic enzyme production may be limiting (Lindemann et al 1986), which is consistent with industry practice. One final point to note is that most research trials have been conducted with older pigs.…”
Section: Pentosans As Growth-depressantssupporting
confidence: 55%
“…p-Glucan is also highly digestible in the ileum of pigs (Graham et al 1986), apparently more digestible than starch (Graham et al 1989) (Thacker et al 1988(Thacker et al , 1992b (Thacker et al , 1992a It seems that the most likely application would be in weanling pig diets where pancreatic enzyme production may be limiting (Lindemann et al 1986), which is consistent with industry practice. One final point to note is that most research trials have been conducted with older pigs.…”
Section: Pentosans As Growth-depressantssupporting
confidence: 55%
“…Attempts have been made to improve the performance of pigs fed barley through enz).rne supplementation. However, supplementation of barley-based diets with B-glucanase have not produced improvements in pig performance comparable to those observed with poultry (Thacker et al 1988(Thacker et al ,1992a.…”
Section: Canadian Journal Of Animal Sciencementioning
confidence: 98%
“…In general, the response to enzyme supplementation of cereal-based diets is significantly higher in younger compared to older animals, with the former group being especially sensitive to the water-soluble and highly viscous carbohydrates. The benefits of enzymes are usually much greater in chicks than in pigs (Graham et al 1986;Bedford et al 1991;Bedford and Classen 1992;Thacker et al 1992;Marquardt et al 1994). It has been suggested that anatomical and physiological differences in the digestive tract of poultry and pigs, mainly the presence of the crop and a lesswell-developed and functional cecum in the former group may be responsible for the difference in response (Campbell and Bedford 1992).…”
mentioning
confidence: 99%